Pengaruh Penggunaan Artificial Intelligence (AI) terhadap Keterampilan Berbicara Kritis dan Menulis Kritis - Hasnatan Hasnatan; Nensilianti Nensilianti; Sultan Sultan (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to determine the effect of using Artificial Intelligence (AI), specifically ChatGPT, on the critical speaking and critical writing skills of Grade X students at UPT SMA Negeri 3 Bone. The research employed a quantitative method with a true experimental design using a pretest-posttest control group model. Data were collected through tests administered before and after the treatment, and analyzed using descriptive and inferential statistics. The results showed a significant improvement in students’ critical speaking skills (from 71.51 to 80.03) and critical writing skills (from 73.96 to 91.33) after the use of AI. T-test results indicated statistically significant differences (Sig. < 0.05) in both paired and independent samples. These findings confirm that AI use is effective in enhancing students’ critical speaking and writing skills.